Inhibitors of cathepsin G: a patent review (2005 to present). (December 2013) - Kosikowska, Paulina; Lesner, Adam
<x xml:space="preserve">Abstract</x> Introduction: Cathepsin G (CatG) is a neutral proteinase originating from human neutrophils. It displays a unique dual specificity (trypsin- and chymotrypsin-like); thus, its enzymatic activity is difficult to control. CatG is involved in the pathophysiology of several serious human diseases, such as chronic obstructive pulmonary disease (COPD), Crohn's disease, rheumatoid arthritis, cystic fibrosis and other conditions clinically manifested by excessive inflammatory reactions. For mentioned reasons, CatG was considered as good molecular target for the development of novel drugs. However, none of them have yet entered the market as novel therapeutic agents. Areas covered: This article presents an in-depth and detailed analysis of the therapeutic potential of CatG inhibitors based on a review of patent applications and academic publishing disclosed in patents and patent applications (1991 – 2012), with several exceptions for inhibitors retrieved from academic articles. Expert opinion: Among the discussed inhibitors of CatG, examples corresponding to derivatives of β-ketophosphonic acids, aminoalkylphosphonic esters and boswellic acids (BAs) could be regarded as the most promising. The most promising one seems to be analogues of compounds of Nature's origin (peptidic and BA derivates). Nevertheless, nothing is currently known about the clinical disposition of any of the CatG inhibitors discovered so far. This latter point suggests that there is still a lot of work to do in the design of stable, pharmacologically active compounds able to specifically regulate the in vivo activity of cathepsin G.